The performance of goats browsing Leucaena leucocephala in the semi arid areas of northwest Venezuela - Clavero, Tyrone; Razz, Rosa (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
A field experiment was conducted in the dryland farming area of northwest Venezuela in order to evaluate three diets in grazing goats (grazing pasture only (buffel grass); grazing pasture + 0.3 kg of commercial concentrate/animal/d; grazing pasture + restricted browsing for two hours daily in Leucaena leucocephala) on milk production, milk composition and growth rate. The data showed significant difference (P < 0.05) between treatments. Daily milk yield increased in 35 and 52.7% when goats had access to commercial concentrate or browsing leucaena as well as grass pasture compared with the control treatment. Daily milk yield in goats with access to leucaena was insignificantly different than goats on concentrate. Treatments did not affect milk composition. The daily growth rate of goats was significantly higher in concentrate (50.5 g) or leucaena (48.4 g) compared to grazing pasture (35.8 g). The results suggest that Leucaena leucocephala can supply an adequate amount of nutrients with similar value to commercial concentrate for growth and milk production without adverse effects on tropical grazing goats.